2013
DOI: 10.4274/tjh.2012.0059
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies and Systemic Scleroderma

Abstract: Objective: Antiphospholipid antibodies (APLs) could be associated with an increased risk of vascular pathologies in systemic scleroderma. The aim of our study was to search for APLs in patients affected by systemic scleroderma and to evaluate their involvement in the clinical manifestations of this disease.Materials and Methods: We conducted a cross-sectional descriptive study, from January 2009 until August 2010, with patients received at the Department of Dermatology (Dakar, Senegal). Blood samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Meta-regression did not find any association between the risk of bias and the prevalence of aPL (Table 6 ). Moreover, the aforementioned analyses were performed in duplicate for the five studies for which both LA, aCL and anti-β2GpI were tested [( 8 , 10 , 22 , 26 ), in this study]. The prevalence of aPL, LA, aCL, and anti-β2GpI were 24% (7–47), 1% (0–4), 11% (4–19), and 10% (1–27), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-regression did not find any association between the risk of bias and the prevalence of aPL (Table 6 ). Moreover, the aforementioned analyses were performed in duplicate for the five studies for which both LA, aCL and anti-β2GpI were tested [( 8 , 10 , 22 , 26 ), in this study]. The prevalence of aPL, LA, aCL, and anti-β2GpI were 24% (7–47), 1% (0–4), 11% (4–19), and 10% (1–27), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Morrisroe et al ., the presence of aPL antibodies is associated with interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), Raynaud’s phenomenon and digital ulcers [ 19 ] and suggests that endothelial abnormalities and small vessel thrombosis may be important in the pathogenesis of these SSc features [ 19 ]. On the other hand, there are some data, which do not find significant differences in clinical manifestations of SSc between the aPL positive and aPL negative group [ 8 ]. However, in the majority of papers, mean serum levels of aPL were below the cut-off values required for the diagnosis of APS, and the issue whether low titre aPL are pathogenic or not in SSc patients is open to debate [ 6 , 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some reports describe, severe vascular complications in SSc patients, such as pulmonary arterial hypertension (PAH), proteinuria, deterioration of kidney function occurring more frequently in aPL positive patients though none of the patients had clinical features of APS [ 10 ]. In the literature available, there are some data about the influence of aPL presence on GFR but no information about long – term influence of aPL antibodies on GFR in patients with SSc [ 5 , 6 , 8 ]. The aim of the study was the assessment of changes in GFR markers during the 24-months observation of a group of SSc patients with and without chronic aPL positivity.…”
Section: Introductionmentioning
confidence: 99%
“…38.9% of patients with SSc had antiphospholipid antibody presence associated with low complement level, in the absence of any clinical feature of APLs. Toure, in his study of 40 pts with SSc identified APLa in 57.3% of them [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%